Specific Features of Modern Innovative Environment in the Republic of Belarus - O. S. Bliznyuck (Наука и техника)
The paper is devoted to study of the modern innovative environment in the Republic of Belarus, its most important characteristics, problem areas. A conceptual apparatus has been given in the paper that determines an innovative environment, institutional conditions that contribute to its formation, priorities for development of research activities have been given and specified in the paper with due account of the requirements for modernization of the economy. The paper presents a definition of the innovation system which is given by distinguished western scientists and researchers who have been seriously engaged in its study. The aim of the research is qualitative, quantitative analysis of the innovation environment of the Republic of Belarus and also a comparative  analysis of  the innovation  environment of  the  Republic of  Belarus, its main  components  (legal, financial support, institutional specific features of function- ning) against the background of Russia and Kazakhstan. The paper contains SWOT-analysis which is used  to find possible directions of  innovative development of  the economy of the Republic  of  Belarus  on the basis of the existing national economic system and taking into account the peculiarities of the national mentality. Attention has been attracted to the fact that such factor of innovative development as “innovative behavior of employees” which is one of the key factors of competitive advantage in the world's leading companies is very important for evaluation and analysis of the innovation environment. The paper presents  an own model of the national innovation  system which consists of three subsystems: human capital, technological infrastructure and innovation support subsystem. Process of creating innovative products  has been shown in the paper and these products make it possible to understand interrelation of  the innovative ideas market  and the market of innovative product. It is proposed to use a categorical apparatus of legal acts of the Republic of Belarus to describe and characterize the markets of innovative ideas and innovative products. The analysis has been performed while using legislative acts, resolutions of the Government of the Republic of Belarus, analytical articles, conference materials, electronic resources, official statistics of the National Statistical Committee of the Republic of Belarus.